A structured exercise to relieve musculoskeletal pain caused by face-down posture after retinal surgery: a randomized controlled trial - A-Young Kim (Nature Portfolio, 2021)
Abstract Face-down posture after vitrectomy physically burdens patients. Despite being of significant concern for patients, the intraoperative pain and discomfort has not been of great interest to retinal surgeons or researchers. This randomized controlled trial evaluated the effect of a 3-day novel structured exercise on reducing musculoskeletal pain from the face-down posture in 61 participants (31 in the exercise group) who underwent vitrectomy. Among the subjects, the median age was 62 years, 42 were female, 42 had macular holes, and 19 had retinal detachments. Participants in the exercise group received initial education on the exercise and performed three daily active exercise sessions. After the sessions, the exercise group had median numeric pain scores of 2, 1, and 1 at the back neck, shoulder, and lower back, respectively, while the control group had corresponding scores of 5, 3, and 4, respectively. The exercise group reported significantly lower pain scores (P = .003, .039, and .006 for the back neck, shoulder, and lower back, respectively). Application of the structured exercise would alleviate the patients’ position-induced postoperative physical burden, by reducing pain and discomfort.